PENERAPAN MANAJEMEN MUTU TERPADU DALAM PENINGKATAN KUALITAS PENDIDIKAN - Yusri M. Daud (STAI Nusantara Kota Banda Aceh, 2026)
Improving educational quality requires a managerial approach that goes beyond document compliance and end-result evaluation by integrating leadership, learning processes, human resource development, data use, and continuous improvement. This article analyses the principles, implementation stages, benefits, and constraints of Total Quality Management (TQM) in improving educational quality. A narrative-analytical literature review was conducted using foundational books, scholarly articles, ISO 21001:2025, international reports, and Indonesian education regulations. Sources were purposively selected for relevance, authority, and contribution to understanding TQM implementation. The review identifies seven interdependent foundations: leadership commitment; learner and stakeholder focus; process management; staff involvement and development; data-informed decision making; continuous improvement; and a quality culture. Effects on learning outcomes are not automatic, but are mediated through better teaching, services, supervision, and collaboration. Effective implementation requires the Plan-Do-Check-Act cycle, balanced indicators, participation across the institution, and consistent follow-up. TQM should therefore be treated as an organizational learning culture and management system rather than merely a certification or quality-administration programme.